Persea americana leaf extract promotes wound healing by inhibiting NF-KB1 - Yunilda Rosa, Riyanto Riyanto, Gita Susanti, Arif Setiawansyah, Zuhana Zuhana, Asih Fatriansari, Saka Agung Pratama (Journal of Applied Pharmaceutical Science, 2025)
Wound healing is a complex process, and there is ongoing interest in identifying natural compounds that can enhance this process effectively. Persea americana has been traditionally used for wound treatment, but its molecular mechanisms remain unclear. This study aimed to evaluate the wound-healing properties of P. americana leaf extract and elucidate its underlying molecular mechanisms through an integrated approach. The research employed a combination of in vivo studies, network pharmacology analysis, and molecular docking simulations. In vivo experiments assessed the wound healing efficacy of P. americana leaf extract at concentrations ranging from 5% to 15%, compared to povidone iodine. Network pharmacology was used to identify potential molecular targets, while molecular docking simulated interactions between key compounds and identified targets. In vivo studies demonstrated that P. americana leaf extract (5%–15%) exhibited wound healing activity comparable to povidone iodine, with no statistically significant differences observed (p value > 0.05). Network pharmacology analysis identified NF-κB1 as a core molecular target in the extract’s wound-healing process. Molecular docking simulations corroborated these findings and highlighted epicatechin, catechin, and quercetin as key compounds likely responsible for the observed wound-healing activity, primarily through NF-κB1 inhibition. This study provides strong evidence for the wound-healing efficacy of P. americana leaf extract and offers insights into its molecular mechanisms, particularly its inhibition of NF-κB1. The findings support the traditional use of P. americana in wound treatment and suggest its potential as a natural alternative in wound management.
Keywords: Persea americana, wound healing, molecular mechanism, in silico, in vivo